Mining repositories to analyze the lifecycle of frameworks and libraries - Gesse Júnior, Ronaldo Rubens; Souza, Higor Amario de (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de Software, 2024)
In a constantly evolving technological landscape, it is crucial to choose the right components and technologies for a software project to ensure its successful development. Frameworks and libraries are essential components that provide functionality to the code and accelerate the development process. They assist teams in delivering results more efficiently to the end user through software reuse. This work proposes using Mining Software Repositories (MSR) to analyze the lifecycle of frameworks and libraries.We aim to understand whether a framework or library is properly updated, maintained, and sought after by the community, which may indicate its lifecycle stage.We explored data from several open source projects: the number of commits and contributors over time. Also, we are using data from Google Trends to explore the developer community’s interest in such libraries and frameworks. We are using a trend metric – Exponential Moving Average (EMA) – over the prior mentioned variables to indicate the lifecycle stage of such frameworks and libraries. The initial results show that our approach can distinguish lifecycle trends for frameworks within the same domain. Our future research will involve examining additional MSR data (such as pull requests, issues, and code changes), obtaining other data sources (Q & A sites), and applying time series Machine Learning techniques to improve the analysis.